An in silico, in vitro and in vivo study of the structural and functional features of SARS small protein E and its contribution to viral morphogenesis and apoptosis. - Torres, Jaume. (2010)
Severe acute respiratory syndrome (SARS) is a respiratory disease in humans caused by the SARS coronavirus (SCoV). All coronaviruses encode a small hydrophobic envelope (E) protein, which mediates viral assembly and morphogenesis by an unknown mechanism. When E proteins are synthesized alone, they reconfigure intracellular membranous organelles or induce secretion of exosomal vesicles when overexpressed. However, their precise function remains elusive. Indeed, although they promote coronavirus assembly, they are not absolutely required. Additionally, it has been found that E proteins of several different coronaviruses, despite having amino acid identities of only about 200/0, substitute for MHV E and provide growth for MHV lacking E. This suggests that E proteins do not have typespecific interacting virion assembly partners, e.g., M or S proteins.